Assessment of aortic regurgitation mechanism with cardiac magnetic resonance: an echocardiography comparative study. (8th February 2021) - Richardson, M; Raad, N; Coisne, A; Ridon, H; Polge, AS; Mouton, S; Silvestri, V; Pagniez, J; Longere, B; Modine, T; Soquet, J; Juthier, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Aortic regurgitation (AR) quantification still remains challenging and requires an integrated approach. AR mechanism is one key parameter to take into account to assess its severity and repairability, and thus help to guide surgical decision. Although Cardiac Magnetic Resonance (CMR) has a growing interest in AR quantification, its performance to identify aortic AR mechanism has never been studied. Purpose: We intended to define CMR Performance in this setting, by using echocardiography as reference. Methods: AR mechanism was systematically evaluated in sixty-seven patients (81% male, mean age 46 ± 20 years) with chronic AR using CMR, and compared to transthoracic (TTE) and transesophageal (TEE) echocardiography as gold standard. AR were categorized as follows: type 1, aortic dilatation; type 2, Cusp prolapse; type 3, restrictive cusp motion. Jet direction, number of cusps and calcification (1 = no calcification, 2 = spots, 3 = big calcification interfering with cusp motion and 4 = Extensive with restricted cusp motion) were also evaluated. Results: At TTE/TEE, mechanisms of AR were type 1 in 56 (83.5%), type 2 in 33 (49.2%), type 3 in 24 (35%). Agreement between TTE/TEE and CMR was modest, with respectively 74.6% (k= 0.4), 79.1% (k = 0.58) and 74.6% (k = 0.44). Bicuspid aortic valve was found in 44 (65.7%) patients at TTE/TEE, agreement with CMR was excellent, 98.5% (k = 0.97).  Jet was directed to the mitral valve in 42 (62.7%), at the inter ventricular septum in 12 (17.9%), and central in 13 (19.4%). Agreement with CMR was correct, respectively 80% (k = 0, 6), 88% (k = 0.62) and 83.5% (K= 0.52). Calcification extension was 1 in 26 (38.8%), 2 in 25 (37.3%), 3 in 11 (16.4%) and 4 in 5 (7.5%). Agreement with CMR was poor, 44.7% (K= 0.28). Conclusion: Accuracy between CMR and TTE/TEE to evaluate chronic AR mechanism and repairability was modest, with lower performance to define calcification extension.